Aspectos argumentativos e polifônicos do operador discursivo ainda - Costa, Ilioni Augusta da (2008)
The research aims at analyzing and describing headlines of the Folha de S. Paulo newspaper, 2006-2007, constituted by the argumentative operator still. Through a linguistic description of a structural perspective, the study is based on the Argumentative Semantics theory (or Enunciation Semantics), having Oswald Ducrot as precursory, which principal function of the language is the argumentation. The language, in this way, is conceived as a game of voices that the announcer either agrees or identifies with or disagrees. The treatment given by NGB is presented and, at length, by the Traditional Grammars (GTs) related to the morpheme still – morphologically classified as adverb, and syntactically considered as an accessory term, and such morpheme is analyzed, from the Theory of Argumentation in the Language (TAL), as discursive operator, linguistic mark that is presented as a strategy which the announcer seizes upon, aiming at the interlocutor adhesion to the announcer’s ideas. The research goal is showing that, although traditionally relegated to a marginal condition by traditional grammars, in studies of the language that operator is recovered by the Argumentative Semantics that acknowledges it as a possessor of great argumentative power, which function in the headlines is fundamental in the construction of senses.